PERKAWINAN ADAT SUKU KAMORO DI TIMIKA PAPUA - Mipitapo, Yohanes Yansen; Mawara, Jetty E. T.; Mulianti, Titiek (Universitas Sam Ratulangi, 2021)
Kamoro people in Mimika regency of Papua Province have a customary custom in the aspect of marriage that is different from other ethnic groups. Kamoro people have myths that are believed to be the power of supernatural above humans. The myths are passed down through generations in oral form, from their ancestors. One of the most famous myths in the Kamoro is Uwao Nani (komodo). In addition, Kamoro believe that the environment also has supernatural powers, objects that are believed to have powers such as the statue of Mbitoro made of wood. Mbitoro is a spirit that is given shape in the form of a statue. Mbitoro engraved pictures of ancestral community leaders who have died. Traditional ceremonies performed by Kamoro people, have a certain meaning or value. Through the initiation rites of karapao in the lives of Kamoro, seen as a traditional social grouping, each individual begins to recognize his or her identity, i. e. into generations and as members of the local community. Through the initiation rites karapao each boy is ushered into social groups and deified in a number of areas of life, namely religion, socioeconomic, sexuality, health and politics, as well as the imposition by bringing back ancestors and mystical figures who have lived in the past. Keywords: marriage, ceremony, ancestors